(untitled) (Bangladesh Heart Journal, 2020)
Background: Endotracheal intubation is an essential primary skill for all anesthesiologists. For cardiac anesthesiologists rapid and proper intubation is more important as failure may cause serious consequences. Video laryngoscope provides a better real time view of the larynx, epiglottis and vocal cords. It also keeps the intubating anesthetist away from the patient as compared to conventional laryngoscopy. This may be very important in this COVID-19 era. To the best of our knowledge the Department of Cardiac Surgery and Cardiac Anesthesia of Chattogram Medical College & Hospital is the first center in Bangladesh to introduce video laryngoscope in cardiac OT. The objective of this study was aimed to compare the intubation time, hemodynamic response to laryngoscopy, success rates and operator’s comfort using the conventional Macintosh laryngoscope and video laryngoscope in adult patients undergoing cardiac surgery. Materials and Methods: A total of 60 adult patients were included in this comparative study, subjected to general anesthesia for cardiac surgery, intubated using either conventional Macintosh direct laryngoscope or video laryngoscope. Patients were intubated by 3 different consultant anesthesiologists with equal competency of our department. Results: There was not much difference between Video laryngoscopy and conventional laryngoscopy in terms of intubation time and success rate. Video laryngoscopy exhibited less hemodynamic response to laryngoscopy and intubation; however, the difference was not statistically significant in this small group of patients. Operators were much more comfortable with Video laryngoscope than conventional laryngoscope particularly with the cases of difficult intubation because of the better glottic view with the former. Conclusion: Video laryngoscope is preferred by cardiac anesthetists because of better glottic view. Bangladesh Heart Journal 2020; 35(1) : 47-53